Who Owns Ancient Art & Architecture? - Moodie, Ashley (MacEwan University Student eJournal, 2024)
The ownership of ancient art and architecture encompasses both public and private spheres and plays a pivotal role in shaping the cultural identity of nations, both past and present. This essay posits that the complex notion of ownership is non-binary, highly nuanced, and that cultural repatriation should be considered on a case-by-case basis. This paper will explore the concept of the universal museum, dissecting its positive qualities and its less flattering aspects, followed by a glimpse into the illicit worldwide antiquities trade and how museums perpetuate the markets’ existence. Finally, the Elgin Marbles case study is exemplified to identify issues from perspectives of both public and private ownership.